ESTIMASI NISBAH PROTEIN-ENERGI PAKAN IKAN SENGGARINGAN (Mystus nigriceps) DASAR NUTRISI UNTUK KEBERHASILAN DOMESTIKASI - Sanjayasari, Dyahruri; Kasprijo, Kasprijo (Fakultas Perikanan dan Kelautan Universitas Riau, 2010)
Senggaringan fish is one of important fisheries resource which needs todevelop in Purbalingga. Unfortunately there were still lacks of domesticationtechnology to support it. One of the most potential aspects to prepare theaquaculture of senggaringan is by preparing the nutrition aspect and feedmanagement. This research has purpose to encourage the effect of protein leveland protein energy ratio in different feed to relative growth, protein retention(PR) and protein efficiency ratio (PER) of senggaringan. The method was usedCompletely Randomize Design with five different feed protein level and energyratio P1 (25;18), P2 (30;13.9), P3 (30; 14.2), P4 (30;15), P5 (35;12) with 4repetitions. The data was collectected for five weeks. The result showed that P4(30;15) had the best performance than other treatments. The best PR and PERalso showed by treatment P4 (P<0.05), 47,14% and 1,52. It means thatsenggaringan fish can accept pellet as their food to fastening the growth. Butthere still need more research to encourage the nutrition composition every phaseand feed management of senggaringan fish to succeed the domestication.